KESANTUNAN BERBAHASA DEWAN JURI RAGAM ACARA “BERAKSI DI RUMAH SAJA” DI INDOSIAR (KAJIAN SOSIOPRAGMATIK) - Muhammad Hasbullah Ridwan; Nurul Khamidah (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Speaking in a good and polite way is a rule in communicating so that communication can run smoothly and the purpose of discussion or the purpose of communication can be achieved. Communication between individuals or groups can occur in various places be it in the family environment, workplace and others. In addition, communications can be found on newspapers, tabloids, wrong magazines and television broadcasts. One of the television shows that shows the existence of communication between people is in various events "BerAKSI at Home Only" in Indosiar. In line with the above, the purpose of this study is to analyze the fulfillment of the principle of language impression, violation of the principle of language impression and see what factors influence the violation of the principle of language impression of the jury variety of events "BerAKSI at Home Only" in Indosiar. This research uses descriptive qualitative research method that describes and presents the data obtained factually and accurately. The data for this study is the speech of the jury of various events "BerAKSI at Home Only" in Indosiar that allegedly fulfilled the principle of language impressionion and violated the principle of language impression. Data collection techniques carried out in this research are listening techniques, note-recording techniques, and data reduction. The results showed the fulfillment of the principle of language impression in (1) the maksim of wisdom, (2) the max of generosity, , (3) the maksim of humility, (4) the maksim of the match, (5) the maksim of pympaness. Furthermore, the results of research on speech that violates the principle of language impressions that are diklasifikaiskan on the factors that cause violations of the principle of language impression (1) because of criticism directly with harsh words, (2) factors of encouragement of the sense of emotion of speakers, (3) factors deliberately accusing the opponent of speech, (5) factors deliberately cornering the opponent as much.